“GOODS CLASSIFICATION AND RISK MANAGEMENT IN CUSTOMS ADMINISTRATION OF THE REPUBLIC OF UZBEKISTAN”. (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2026)
This article analyzes the classification of goods within the Commodity Nomenclature of Foreign Economic Activity of the Republic of Uzbekistan, based on the Harmonized System developed by the World Customs Organization. It examines the key principles of classification, identifies common challenges and errors, and highlights the role of risk management systems in ensuring accurate customs declarations. The study emphasizes the importance of proper classification for determining customs payments and concludes that the integration of modern technologies and risk-based approaches improves the efficiency of customs administration.